Direct ink writing of catalytically active UiO-66 polymer composites. Issue 15 (31st January 2019) - Young, Adam J.; Guillet-Nicolas, Rémy; Marshall, Ellis S.; Kleitz, Freddy; Goodhand, Alex J.; Glanville, Lloyd B. L.; Reithofer, Michael R.; Chin, Jia Min
Abstract : Highly catalytic 3D printed UiO-66 composite affords ease of use and clean-up for degradation of nerve agent simulant. Abstract : Metal–organic frameworks (MOFs) hold significant potential for use in gas storage, sensing and catalysis. To uncover this potential, MOF processing must develop in line with MOF materials. Here, direct ink writing-based 3D printing of UiO-66 MOF composites and their thermal treatment give mechanically stable yet highly porous composites effective for the catalytic breakdown of methyl-paraoxon, a simulant of highly toxic organophosphate nerve agents.